KEMAMPUAN PEMAHAMAN KONSEP SISWA PADA PEMBELAJARAN MATEMATIKA MENGGUNAKAN MODEL GENERATIVE LEARNING DI KELAS VIII SMP NEGERI 6 PALEMBANG - Maharani, Levana; Hartono, Yusuf; Hiltrimartin, Cecil (Mathematics Education Journal, 2013)
This study aims to determine the ability to understand students' concepts on learning mathematics using generative learning model. This research is a descriptive research. Subjects in this study were students of class VIII.2 SMP Negeri 6 Palembang with the number of students 27 people. Data retrieval is done by using test. The data used in this research is the data of the ability of concept comprehension after doing the test questions to measure students' concept comprehension ability. Problem test is given after the learning process and refers to the concept of understanding indicators. Based on the results of the study concluded that the ability to understand the concept of students who learn with generative learning model is quite good. DOI: https://doi.org/10.22342/jpm.7.2.4650.1-16